Large-scale chemical vapor deposition growth of highly crystalline MoS2 thin films on various substrates and their optoelectronic properties - Nguyen, Van Tu; Ha, Seongju; Yeom, Dong Il; Ahn, Yeong Hwan; Lee, Soonil; Park, Ji Yong (Current Applied Physics, 2019)
Large-scale growth of mostly monolayer molybdenum disulfide (MoS2) on quartz, sapphire, SiO2/Si, and waveguide substrates is demonstrated by chemical vapor deposition with the same growth parameters. Centimeter-scale areas with large flakes and films of MoS2 on all the growth substrates are observed. The atomic force microscopy and Raman measurements indicate the synthesized MoS2 is monolayer with high quality and uniformity. The MoS2 field effect transistors based on the as-grown MoS2 exhibit carrier mobility of 1–2 cm2V−1s−1 and On/Off ratio of ~104 while showing large photoresponse. Our results provide a simple approach to realize MoS2 on various substrates for electronics and optoelectronics applications.
Keywords: Growth substrates; Molybdenum disulfide; MoS2; Optoelectronic properties; Photoresponses; Raman measurements; Various substrates; Waveguide substrates; CVD; FET; Monolayer; MoS2; Photoresponse